ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP PENCIPTA LAGU ATAS TINDAKAN COVER MELALUI MEDIA SOSIAL BERDASARKAN UNDANG-UNDANG HAK CIPTA - SUPARLAN SUPARLAN; ZUBAEDI ZUBAEDI (GANEC SWARA, 2024)
Legal protection is an obligation that must be fulfilled by the government to provide a sense of security to the public, one of which is legal protection in the field of copyright relating to musical works of art. This research is motivated by the many cases that occur in society related to copyright violations in the music sector, namely illegal song covers via the YouTube platform and other social media, content creators or YouTubers earn income from the adsens of the videos they upload while on the other hand this detrimental to the songwriters or copyright holders of the song. The formulation of the problem in this research is what is the legal protection for songwriters for covering acts via social media platforms based on copyright law, what actions can be taken by songwriters for covering acts via social media platforms based on copyright law, This research was conducted using a normative method using a statute approach and a conceptual approach and a problem approach. The results of this study provide legal protection for songwriters for cover acts through the YouTube platform based on Law No. 28 of 2014 and preventive efforts made by the government through the Ministry of Communication and Information (Kemenkominfo) to regulate YouTube channels or other social media by blocking them and then applying pressure (repression) such as compensation to requesting a stop to illegal cover activities of the works produced.